2016
DOI: 10.1063/1.4966922
|View full text |Cite
|
Sign up to set email alerts
|

Non-exponential kinetics of unfolding under a constant force

Abstract: We examine the population dynamics of naturally folded globular polymers, with a super-hydrophobic "core" inserted at a prescribed point in the polymer chain, unfolding under an application of external force, as in AFM force-clamp spectroscopy. This acts as a crude model for a large class of folded biomolecules with hydrophobic or hydrogen-bonded cores. We find that the introduction of super-hydrophobic units leads to a stochastic variation in the unfolding rate, even when the positions of the added monomers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The subunit, which is temporarily bound to the cavity, resists the filament movement, the www.nature.com/scientificreports www.nature.com/scientificreports/ associated counter-torque slowing down its natural rotation in the motor. The motor exerts an equal and opposite force on the substrate, helping it overcome the energy barrier and unfold (a number of studies give details of protein unfolding under force [42][43][44].…”
Section: Assisted Unfoldingmentioning
confidence: 99%
See 1 more Smart Citation
“…The subunit, which is temporarily bound to the cavity, resists the filament movement, the www.nature.com/scientificreports www.nature.com/scientificreports/ associated counter-torque slowing down its natural rotation in the motor. The motor exerts an equal and opposite force on the substrate, helping it overcome the energy barrier and unfold (a number of studies give details of protein unfolding under force [42][43][44].…”
Section: Assisted Unfoldingmentioning
confidence: 99%
“…In the stall mode the rotation of the motor is fully blocked by the substrate which is able to apply G stall to the motor. This counter-torque builds up tension in the subunit protein, until it unfolds with the help of other mechanisms such as chaperones 1,4 , or just stochastically 43,44 . Mean first-passage time can be used to calculate the average time for such stochastic unfolding.…”
Section: Assisted Unfoldingmentioning
confidence: 99%
“…The subunit, which is temporarily bound to the cavity, resists the filament movement, the associated counter-torque slowing down its natural rotation in the motor. The motor exerts an equal and opposite force on the substrate, helping it overcome the energy barrier and unfold (a number of studies give details of protein unfolding under force [43][44][45] ).…”
Section: Assisted Unfoldingmentioning
confidence: 99%
“…In the stall mode the rotation of the motor is fully suppressed by the substrate which is able to apply G stall to the motor. This counter-torque builds up tension in the subunit protein, until it unfolds with the help of other mechanisms such as chaperones 1,4 , or just stochastically 44,45 . Mean first-passage time can be used to calculate the average time for such stochastic unfolding.…”
Section: Assisted Unfoldingmentioning
confidence: 99%
“…However, several studies have shown that the resulting empirical distributions did not follow the Poisson distributions ( Brujic et al., 2006 , 2007 ; Garcia-Manyes et al., 2007 ). This observation led to an effort to explain the measured deviation from exponentiality by means of static and dynamic disorders ( Kuo et al., 2010 ; Chatterjee and Cherayil, 2011 ; Zheng et al., 2014 ; Costescu et al., 2017 ; Kundu et al., 2020 ), corrugated energy landscapes ( Brujic et al., 2006 ; Lannon et al., 2012 ), and as consequence of the polymeric nature of the proteins ( Bell and Terentjev, 2016 ). In their pioneering computational work, Bura et al., showed how unfolding in polyproteins become less correlated when reducing the applied force from 88 to 66 ​pN ( Bura et al., 2007 , 2008 ).…”
Section: Introductionmentioning
confidence: 99%